Immunomodulation of Murine Macrophages RAW264.7 Infected with Mycobacterium Smegmatis - Nur Ayuni, Kadir; Nur Ain, Mohd Asr; Armando, Acosta; Maria, E. Sarmieto; Mohd Nor Norazmi, . (Penerbit Universiti Sultan Zainal Abidin, 2020)
Tuberculosis (TB) remains as a major worldwide health problem which cause more than 1.3 million deaths annually. The search for new vaccines more efficacious than Bacille Calmette- Guѐrin (BCG) for TB prevention is regaining importance to control the disease. Mycobacterium smegmatis (Ms), which shares genetic and structural homology with virulent mycobacteria, showed extensive advantages in vaccine vector development. In addition, autophagy has emerged as a major immune mechanism against pathogens in macrophages. The aim of this study is to determine immunomodulation capacity of Ms as a possible vector in development of vaccine candidates against TB. The immunomodulatory capacity of Ms were evaluated in RAW 264.7 murine macrophages cell line. The intracellular uptake were assayed by Ziehl- Neelsen staining and its phagocytic index (PI) were evaluated. The supernatant were used to determine cytokine production (IFN-γ and IL-1β). In general, the results demonstrated the immunomodulation effects of Ms in macrophages. For PI, a significant phagocytosis activity was observed in Ms (61.67 ± 2.84) compared to uninfected group. A significant production of IFN-γ (51.17 ± 20.70) but insignificant IL-1β (370.34 ± 6.23) cytokines were observed compared to uninfected group. The results showed that Ms could induce the immunomodulatory effects on RAW 264.7 murine macrophages. Taken together, this study provides preliminary results of potential evaluation of Ms as a new vector for experimental vaccine development against TB.